Pengaruh Diskontinuitas Terhadap Kestabilan Lereng Batuan Terkekarkan Studi Kasus Kuari Andesit PT Lola Laut Timur Kabupaten Bogor - Irwan, Andesta Granitio; Koesnaryo, S.; Dwinagara, Barlian; Saptono, Singgih (PROMINE, 2021)
Discontinuity in a rock mass has an influence on the stability of a rock slope because it is one of the controlling factors of slope failure. In this study, an analysis was carried out on the role of discontinuities, namely joints and lithic tuff layers on slope stability and the effect of persistent parameters and joint roughness on the safety factor of safety factor. The analysis used is the effect of changes in the thickness of the lithic tuff, persistence and the value of joint roughness on the value of the safety factor. Processing of slope stability data using Rocscience RS2 Software with Finite Element Method modeling with rock mass modeling used in the analysis, namely the Veneziano Model. The results showed that an increase in the thickness of the lithic tuff layer resulted in a decrease in the safety factor of the slope up to 1.37%. The effect of the persistence parameter on the slope safety factor was found that the higher the persistence value, the lower the slope safety factor value up to 2,9% and changes in the JRC value decreased the safety factor value up to 1,7%.